Transradial versus Transfemoral Access and the Risk of Acute Kidney Injury following Primary Percutaneous Coronary Intervention in Patients with ST-Elevation Myocardial Infarction: A Systematic Review and Meta-Analysis of Randomized Controlled Trials and Propensity-Score-Matched Studies - Gaspar Del Rio-Pertuz; Michel Juarez; Poemlarp Mekraksakit; Kanak Parmar; Mohammad M. Ansari (Journal of Interventional Cardiology)
Objectives. The aim of this study is to examine the association between vascular access sites and the incidence of AKI in patients with STEMI undergoing primary PCI. Background. Emerging evidence has suggested that transradial access (TRA) may be associated with lower rates of acute kidney injury (AKI) as compared with transfemoral access (TFA). However, most of these studies have included a nonselected study population undergoing diagnostic cardiac catheterization or percutaneous coronary intervention (PCI). Data on the association between TRA and AKI in this setting of STEMI are limited and with conflicting results. Methods. We systematically searched PubMed, Embase, and Scopus for abstracts and full-text articles from inception to July 13th of 2021. Studies included were randomized controlled trials (RCTs) and propensity-score-matched (PSM) studies evaluating the association of TRA versus TFA access with AKI in patients undergoing primary PCI for STEMI. Data were integrated using the random effects model and generic inverse‐variance method of DerSimonian and Laird. Results. A total of 10,093 studies were found. After applying our inclusion criteria, 5 studies from 2014 to 2021 with a total of 8,536 STEMI patients were included. TRA was not significantly associated with a reduced risk for AKI compared with TFA (odds ratio 0.85, 95% CI 0.71–1.01, p 0.07, I2 = 40%). Conclusions. Transradial access was not significantly associated with lower risk of AKI in patients undergoing primary PCI for STEMI compared with TFA. Larger studies are needed to clarify this outcome.